1994
DOI: 10.1002/j.1460-2075.1994.tb06888.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein splicing: an analysis of the branched intermediate and its resolution by succinimide formation.

Abstract: Protein splicing involves the excision of an internal domain from a precursor protein and the ligation of the external domains so as to generate two new proteins. Study of this process has recently been facilitated by the isolation of a precursor and a branched intermediate from a thermophilic protein splicing element expressed in a foreign protein context. Two aspects of protein splicing are examined in this paper. We demonstrate a succinimide at the C‐terminus of the spliced internal protein, implicating cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
142
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 24 publications
3
142
0
4
Order By: Relevance
“…Recently, Chong et al (21) also reported that a branched intermediate accumulated in vivo using the N737A/ C738S mutant of VDE. Our results are consistent with the succinimide-mediated cleavage model at the C-terminal junction (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, Chong et al (21) also reported that a branched intermediate accumulated in vivo using the N737A/ C738S mutant of VDE. Our results are consistent with the succinimide-mediated cleavage model at the C-terminal junction (20).…”
Section: Discussionsupporting
confidence: 92%
“…C-terminal Splice Junction-Asn 737 at the C-terminal junction plays a critical role in protein splicing to form a succinimide ring (20). Cooper et al (12) reported that substitutions of Asn 737 to seven other amino acids (Lys, Ala, Tyr, Gln, Glu, His, and Asp) all resulted in nonspliced products.…”
Section: Discussionmentioning
confidence: 99%
“…When an intein BI accumulates, the (thio)ester linkage is usually alkaline labile at elevated temperatures. 5,[18][19][20] The affinity purified Asn343Ala BI was incubated overnight in vitro at 4 C, room temperature, 30 C or 37 C, pH 6 or 9, and in the presence or absence of 50 mM DTT [ Fig. 5(A) and data not shown].…”
Section: Characterization Of the Branched Intermediate That Accumulatmentioning
confidence: 99%
“…Historically, intein BIs accumulate when the branch point is an ester rather than a thioester, 18,19 so a triple mutant consisting of Cys323Ser, Asn343Ala, and Thrþ1Ala was constructed. A slowly migrating band accumulated in this triple mutant [ Fig.…”
Section: Trapping the Block F Branched Intermediatementioning
confidence: 99%
“…1). Xu et al (1994) demonstrated that the C-terminal end of the VDE protein is Asn737. Finally, Kawasaki et al (1996) determined the junction site of the in vitro spliced recombinant Vma1 protein (peptide E; see Fig.…”
Section: The Vma1 Gene Contains Genetic Information For the Two Protementioning
confidence: 99%